Self‐Organization Principles of Cell Cycles and Gene Expressions in the Development of Cell Populations. Issue 7 (16th May 2021) - Wang, Xiaoliang; Bai, Dongyun
Abstract: A big challenge in current biology is to understand the exact self‐organization mechanism underlying complex multi‐physics coupling developmental processes. Using multiscale computations of subcellular gene expressions and cell population dynamics that are based on first principles, it is shown that cell cycles can self‐organize into periodic stripes in the development of E. coli populations from one single cell, relying on the moving graded nutrient concentration profile, which provides directing positional information for cells to keep their cycle phases in place. Resultantly, the statistical cell cycle distribution within the population is observed to collapse to a universal function and shows a scale invariance. Depending on the radial distribution mode of genetic oscillations in cell populations, a transition between gene patterns is achieved. When an inhibitor–inhibitor gene network is subsequently activated by a gene‐oscillatory network, cell populations with zebra stripes can be established, with the positioning precision of cell‐fate‐specific domains influenced by cells' speed of free motions. Such information may provide important implications for understanding relevant dynamic processes of multicellular systems, such as, biological development. Abstract : Using multiscale physical models, it is revealed that cell cycles and oscillating gene expressions self‐organize into ordered spatial structures according to the moving graded positional information, and cell cycle stripes follow a scale‐invariant statistical distribution. The establishment of zebra stripes further shows significant roles of inhibitor–inhibitor gene network and slow free motions of cells in precise self‐assembly of cell‐fate‐specific regions.